Reconstrução por série focal do Telureto de Bismuto utilizando microscopia eletrônica de transmissão de alta resolução - Thais Milagres de Oliveira (2015)
High-resolution transmission electron microscopy is turning into a very powerful technique in crystal structure determination. Nowadays there are at least two different approaches: electron diffraction, similar to X-ray diffraction and structure determination by through focal series reconstruction of high-resolution transmission electron microscopy images. Additionally, scanning transmission electron microscopy (STEM), with electron energy loss spectroscopy (EELS) in high-resolution transmission electron microscopes with aberration correctors and monochromator have shown good results in many cases. However, high-resolution images interpretation and quantification is complex, due to strong radiation-matter interaction. Besides, the samples exit wave is modified by the microscope, so the contrast observed in the image represents an interference effect and cannot be interpreted directly. To perform this research two materials were used, Silicon, which is well known in the literature and Bismuth Telluride, a thermoelectric material and topological insulator. The main aim of this research is establish the focal series reconstruction procedure for bismuth telluride and in the near future try to determine the atomic positions of intercalated bismuth telluride with tin, selenium and other elements.